Pratiques religieuses dans un sanctuaire véliocasse : les Mureaux à Authevernes (Eure) - Myriam Michel; Yves-Marie Adrian; Jean-Marc Doyen; Alice Hanotte; Tarek Oueslati; Nicolas Roudié (Gallia)
In 2008-2009, the Archeopole company conducted a preventive excavation on a 1.6 ha area, in the Mureaux quarry, at Authevernes (Eure). This operation, the last of a series of archaeological investigations on this site since the mid-1990s, uncovered the remains of an ancient sanctuary. The excavations helped define this cult place’s establishment and functioning chronology between the Tibero-Claudian era and the first decades of the 3rd c. AD. They also permitted some reflections on its status and gave the opportunity to study different traces of cult activity highlighted into the sanctuary: banquets, sacrifices, ritual pits, sediments… These vestiges are diverse and sometimes hard to interpret, but it seems this place was a small rural sanctuary, linked to one or several villae and structured in several cultual activity places. There remains the question of Gallic presence under the sanctuary and of its precise nature.